A novel Mutein of TNFα Containing the Arg-Gly-Asp Sequence Shows Reduced Toxicity in Intestine. Issue 2 (1994) - Shikama Shikama, H. H.; Miyata Miyata, K. K.; Sakae Sakae, N. N.; Kuroda Kuroda, K. K.; Nishimura Nishimura, K. K.; Yotsuya Yotsuya, S. S.; Kato Kato, M. M.
Abstract : The effects of human tumour necrosis factor-α (TNFα), or its mutein (F4168) having the cell adhesive Arg-Gly-Asp sequence at the N-terminus, on intestinal injury, were examined. Histopathological examination revealed that an intravenous injection of TNFα resulted in marked haemorrhage or oedema in the caecum of rats, whereas F4168 showed no such effects even at the same therapeutic dose. Moreover, the number of neutrophils that adhered to endothelial cells or infiltrated the mucosal tissue was much higher after TNFα injection compared with F4168 in vivo . The enhanced adhesion of neutrophils on to human umbilical vein endothelial cells also occurred when the latter were pre-stimulated with TNFα but not with F4168 in vitro . The expression of the cell adhesion molecules including endothelial leukocyte adhesion molecule-1 or intercellular adhesion molecule-1 on F4168- stimulated human umbilical vein endothelial ceils was significantly lower than that stimulated with TNFα. These results suggest that the Arg-Gly-Asp sequence introduced into the TNFα molecule abrogates the side effect of this cytokine such as tissue injury or shock, and that F4168 could be useful for systemic therapy.